Nurses’ Experience With End-of-Life Care in Geriatric Centers: A Systematic Review - Falah Jamal Dakka RN, BSN, MHM, PhD (SAGE Open Nursing)
Background Geriatric nurses provide end-of-life care based on the five pillars of aging. This systematic review assesses the emotions and feelings of geriatric nurses during end-of-life care. It considers the prevalence, triggers, and intensity of emotional responses among geriatric nurses. It also expounds on the strategies for overcoming the emotional challenges. Methods The study embarked on a systematic review of literature materials on nurses’ emotions and feelings. The eligibility criteria involve literature materials published in the past 5 years, peer reviews, English language, geriatric nurses, and nurses in emergency department, primary care, and intensive care unit. Three databases (Cochrane Library, PubMed, and CINAHL) and Google Scholar were used. Results Using a PRISMA flow chart, the literature search led to the discovery of nine significant writings on the emotions and feelings of nurses attending to geriatric patients. Sample sizes in these studies varied from 6 to 126 nurses while three articles involved integrated, scoping, and literature review of published studies. The common emotions and feelings among nurses caring for elderly patients in the geriatric center are compassion fatigue, burnout, grief, and moral distress. Conclusion These emotions and feelings affect the performance of nurses. They also influence their physical and mental wellbeing. This situation calls for developing effective coping strategies to address this challenge.